Defining Price Stability: Public Accountability of the European Central Bank’s Goal Independence - Mattias Vermeiren (Politics and Governance)
The persistent undershooting of its self-defined target to achieve inflation “below but near two percent” prompted the European Central Bank (ECB) to launch a review of its monetary policy strategy and adopt a symmetric inflation target. In this article, I examine the politics of accountability underlying the ECB’s re-definition of its price stability objective through a comparison with the strategy review of the Federal Reserve, which went further than the ECB by setting an average inflation target that intentionally seeks to pursue periods of above-target inflation to compensate for periods of below-target inflation. Drawing on a reputational perspective on public accountability, I elaborate two arguments. First, the ECB decided to engage in a strategy review and revise its inflation target to restore its performative and technical reputation in the face of its persistent undershooting of its inflation target in the decade after the great financial and euro crisis. Second, the presence of a stronger “deflationary bloc” in the region constrained the ECB in adopting an average inflation target and its associated make-up strategy without tarnishing its socio-political reputation.